2021
DOI: 10.1128/spectrum.00182-21
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A H1N1 Induced Disturbance of the Respiratory and Fecal Microbiome of German Landrace Pigs – a Multi-Omics Characterization

Abstract: Here, we used swine as a biomedical model to elucidate the impact of influenza A H1N1 infection on structure and function of the respiratory and gastrointestinal tract microbiome by employing a multi-omics analytical approach. To our knowledge, this is the first study to investigate the temporal development of the porcine microbiome and to provide insights into the functional capacity of the gastrointestinal microbiome during influenza A virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 82 publications
3
25
1
Order By: Relevance
“…In order to test the reproducibility of the proposed workflow, we computed the size of intersection between the microbial families reported to be instrumental in Borey et al ( 2021 ) and Gierse et al ( 2021 ) and the ones found by applying our workflow to these two datasets. The sequences of the first dataset (Borey et al, 2021 ) were downloaded from the NCBI Sequence Read Archive using accession number PRJNA647267 and processed using SHAMAN tool (Volant et al, 2020 ) in order to obtain the OTU abundance matrix and annotation table.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to test the reproducibility of the proposed workflow, we computed the size of intersection between the microbial families reported to be instrumental in Borey et al ( 2021 ) and Gierse et al ( 2021 ) and the ones found by applying our workflow to these two datasets. The sequences of the first dataset (Borey et al, 2021 ) were downloaded from the NCBI Sequence Read Archive using accession number PRJNA647267 and processed using SHAMAN tool (Volant et al, 2020 ) in order to obtain the OTU abundance matrix and annotation table.…”
Section: Resultsmentioning
confidence: 99%
“…The sequences of the first dataset (Borey et al, 2021 ) were downloaded from the NCBI Sequence Read Archive using accession number PRJNA647267 and processed using SHAMAN tool (Volant et al, 2020 ) in order to obtain the OTU abundance matrix and annotation table. In case of the second experiment (Gierse et al, 2021 ), We used the sequence data obtained from the fecal samples of healthy and infected cohorts. Supplementary Figures 5A , B show that we achieved descent Jaccard similarity coefficient scores 0.70 and 0.66 for these two datasets, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the rhythmic patterns of metabolic genes were not entirely regulated by their core clock, we hypothesized that the gut microbiota played a role in modulating the host peripheral circadian clock and downstream genes. Intriguingly, we found that the HF altered the diurnal rhythm of gut microbiota in a diverse manner, which we classified into three categories: (1) phase shift: contrary to the phase-advanced circadian clock in the liver and WAT, the relative abundance of butyric acid-producing family Clostridiaceae_1 was significantly phase-delayed in the HF group compared with the Ctr group ( 50 ); (2) loss rhythmicity: Veillonellaceae and Prevotellaceae have been confirmed to be responsible for producing SCFAs ( 51 , 52 ), and both lost rhythmicity in the HF group; (3) gain rhythmicity: the families Erysipelotrichaceae and Ruminococcaceae both gained rhythmicity in the HF group compared with the Ctr group. The study has revealed that Erysipelotrichaceae accelerated cholesterol accumulation by producing trimethylamine N -oxide, indicating its role in modulating lipid metabolism ( 53 ).…”
Section: Discussionmentioning
confidence: 99%